Chinese Bridal Makeup and Fashion: A Blend of Modernity and Tradition on The Sangjit Day - Wanda Zefanya; Hamidah, Inggrita; Hidayah, Fitriya Nur; Tiara, Desia Nova; Krisnawati, Maria; Ratri, Pramesti Adika; Hidayati, Ratna (Jurnal Tata Rias, 2025)
This article examines Chinese bridal makeup and attire in the Sangjit procession as a fusion of modern and traditional elements. Sangjit, which is a proposal tradition in Chinese culture, is not only symbolic of the commitment between families, but also rich in visual symbolism through bridal makeup and attire. This study uses a literature review method, referring to various academic articles from Google Scholar to analyze the philosophy, techniques, and dynamics of aesthetic transformation in the Sangjit procession. The results of the discussion show that both makeup and clothing have undergone significant developments: traditional makeup, which used to be colorful, is now more adaptive to global trends, while clothing such as cheongsam retains classic motifs but is processed with modern cuts and materials. This study also reveals that this combination reflects the cultural strategy of the Chinese community to maintain the continuity of tradition amid the tide of modernization. This research contributes to broadening our understanding of cross-cultural aesthetic practices and offers new insights into how cultural identity is articulated through makeup and fashion. However, this study has limitations due to the lack of primary data, so further research using a field approach is highly recommended.